Fodder and grain yield potential of little millet (Panicum sumatrense Roth ex Roem. & Schult.) race robusta and identification of trait-specific germplasm for crop improvement - Vetriventhan, Mani; Jagadeesh, Kommineni; Naresh D.; Singh, Kuldeep (Springer, 2025)
Little millet is one of the small millets native to India, used for both food and fodder purposes. Among the two races (nana and robusta) of little millet, race robusta has a robust growth habit and produces high biomass and grain yield but matures late compared to race nana. In this study, 126 accessions belonging to the race robusta conserved in the ICRISAT Genebank were evaluated during two rainy seasons for fodder and grain yield potential, for the identification of trait-specific germplasm for little millet improvement. Residual maximum likelihood analysis revealed significant variability for all traits evaluated in the individual seasons and pooled for the two seasons. High heritability was observed for most traits in the individual seasons and the pooled data for the two seasons. Principal component analysis revealed the existence of genetic diversity and identified the key traits that contributed to maximum variability. Cluster analysis revealed two major clusters that could form the basis for selecting diverse genotypes for breeding programs. Based on the pooled data, the top 20 accessions each for high grain yield and fodder yield (stover dry weight) were identified, of which accessions IPmr 880, IPmr 871, IPmr 875, IPmr 896 and IPmr 907 were identified for dual purposes (grain and fodder), whereas accessions IPmr 702, IPmr 873, IPmr 876, IPmr 913, and IPmr 1056 were the top five in terms of stover dry weight yield. Multi-location testing of identified sources for yield and adaptation and their use in breeding programs aids in little millet improvement and cultivar releases.